E-Government Implementation Planning in The Foreign Ministry in XYZ Village Government Indonesia - Permana, Budi; Muhammad Indika Fathiras Azhami; Purwadi (JESII: Journal of Elektronik Sistem InformasI, 2024)
The implementation of e-Government has become a commitment of the Government as set out in Presidential Instruction No. 3 of 2003 on national policies and strategies for the development of the e-government, stating that each Regional Government can take the necessary measures in accordance with its main tasks, functions, and authority to implement the development and development of government services based on Information and Communications Technology (ICT) nationally. In support of the implementation of e-Government in the area must of course start from the smallest government of the village. The village is the smaller part of the administrative government system in Indonesia, according to the Law No.6 Year 2014 about the village states the maintenance of the government of village using information technology can be done through e-Governance Village. The implementation of e-Government requires an in-depth study of a suitable model for this village's e-government. The research methods used in the Research are Qualitative Methods, the process of identification of the e-Government needs of the village is carried out with the COBIT 4.1 Framework, Critical Success Factor (CSF), and SWOT analysis. The results of the analysis produce Maturity Level to find out the existing condition of the XYZ Village Government towards e-government, and proposes the implementation plan of e-governing to the XYZ Village Government.